2020
DOI: 10.5005/jp-journals-10024-2735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Translucency of Monolithic Zirconia

Abstract: Aims and objectives: New techniques are being developed to invent zirconia with high translucency and better esthetics leading to the development of several brands of monolithic zirconia. The aim of this study is to compare the translucency of three brands of zirconia available for the fabrication of monolithic restorations. Materials and methods: An in vitro study was designed to compare the translucency of three brands of zirconia available for the fabrication of monolithic restorations: Zirlux Zirconia (Viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies, 28,39 evaluated the translucency of different monolithic zirconia brands. They reported that the translucency of monolithic zirconia is highly affected by the zirconia brand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, 28,39 evaluated the translucency of different monolithic zirconia brands. They reported that the translucency of monolithic zirconia is highly affected by the zirconia brand.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were aged in coffee solution between 5 and 55°C for 5,000 cycles with a dwell time of 30 and 10 s transfer time 39,40 . The coffee solution (Nescafe Classic; Nestle, SA) was produced following the manufacture ’ s recommendation by brewing a spoon of coffee in 177 ml hot water and was refreshed every 12 h. The specimens were brushed circumferentially under running water, for 10 times with toothpaste (Sensodyne; GalaxoSmithKline) and dried to lessen surface stains.…”
Section: Methodsmentioning
confidence: 99%
“…Liebermann et al proved that lithium disilicate ceramics show higher transmittance than all zirconia materials 27) . The crystalline pattern and molecular composition of IPS e.max CAD and IPS Empress CAD makes them more translucent than Zenostar [28][29][30] . In another study, the translucency of Zirconia is related to the changes in composition and sintering parameters 31) .…”
Section: Discussionmentioning
confidence: 99%
“…According to several manufacturers, the thickness of their translucent monolithic Zr dental restorative material can be as thin as 0.3 mm, falling between 0.3 and 0.7 mm. More retentive preparation designs and data about the thickness of translucent monolithic Zr are nevertheless needed and should be included in the literature [47,48]. A careful and accurate reduction of tooth tissue is necessary to get effective results with aesthetic veneers.…”
Section: Veneer Preparation Design Marginal Fit and Adaptationmentioning
confidence: 99%